2001
DOI: 10.1007/s002390010229
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Stages of Protein Evolution as Suggested by Protein Sequence Analysis

Abstract: Evolution of proteins encoded in nucleotide sequences began with the advent of the triplet code. The chronological order of the appearance of amino acids on the evolution scene and the steps in the evolution of the triplet code have been recently reconstructed (Trifonov, 2000b) on the basis of 40 different ranking criteria and hypotheses. According to the consensus chronology, the pair of complementary GGC and GCC codons for the amino acids alanine and glycine appeared first. Other codons appeared as complemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 35 publications
4
62
0
Order By: Relevance
“…We observed that small peptides of 900-1,200 Da in size are more prevalent than other components; the second most abundant group of peptides is the K ϩ channel blockers (3-to 4-kDa peptides), followed by the 6-to 7-kDa peptides classically targeting the Na ϩ channels that are the least abundant group in the prevenom. It is noteworthy to mention that this pattern is in agreement with the general evolutionary formula of ''from simple to more complex'' (28).…”
Section: Discussionsupporting
confidence: 87%
“…We observed that small peptides of 900-1,200 Da in size are more prevalent than other components; the second most abundant group of peptides is the K ϩ channel blockers (3-to 4-kDa peptides), followed by the 6-to 7-kDa peptides classically targeting the Na ϩ channels that are the least abundant group in the prevenom. It is noteworthy to mention that this pattern is in agreement with the general evolutionary formula of ''from simple to more complex'' (28).…”
Section: Discussionsupporting
confidence: 87%
“…The primordiality of TCN codons compared with AGY codons at conserved positions (11,12) and the species segregation of the lineages indicate that the TCN lineage was older and gave rise to the AGY lineage. We used the method previously described for serine protease lineages (6) to identify the "parent inhibitor" (the modern inhibitor most similar to the putative ancestral inhibitor) for the AGY lineage.…”
Section: Resultsmentioning
confidence: 99%
“…The nature of the very first peptides has been indicated and the reasons for the assignment have been presented [154,155]. These very first peptides supposedly were (Ala) 7 and (Gly) 7 , encoded by (GCC) 7 and (GGC) 7 , the two strands of the earliest RNA duplex genes [154,155].…”
Section: (Pre)genetics and (Pre)metabolismmentioning
confidence: 99%
“…These very first peptides supposedly were (Ala) 7 and (Gly) 7 , encoded by (GCC) 7 and (GGC) 7 , the two strands of the earliest RNA duplex genes [154,155]. Hence the relevance of GCCn*GGCn replication studies.…”
Section: (Pre)genetics and (Pre)metabolismmentioning
confidence: 99%